Desain Ragam Hias Batak dalam Konteks Seni dan Desain Kontemporer : Studi Literatur - Rahmi Rahmi; Winda Bali Ulina Tarigan; Hanna Anggraeni Munthe; Lilis Morina Sinulingga (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study explores the adaptation of Batak ornamental motifs from physical artifacts to digital media as a means of preserving cultural identity amid the pressures of modernization. Employing a qualitative method with a systematic literature review approach, the research analyzes 20 selected sources consisting of design journals, anthropological studies, and visual artifact documentation published within the last ten years. The analysis is conducted thematically to map visual structures, shifts in meaning, and adaptation strategies. The key findings indicate that the visual structure of gorga possesses a geometric syntax compatible with modern design principles such as minimalism and grid systems, facilitating its transformation into graphic elements and user interface components. Nevertheless, the study finds that adaptation without philosophical reinterpretation risks the desacralization of symbolic meanings. Therefore, this research recommends digital preservation strategies through augmented reality technologies and collaborative design approaches as solutions to maintain the relevance and sustainability of Batak visual heritage within the global creative industry ecosystem.